Eragon [videorecording (DVD)] - Fangmeier, Stefan M.; Speleers, Ed, 1988-; Irons, Jeremy, 1948-; Guillory, Sienna, 1975-; Paolini, Christopher (20th Century Fox Home Entertainment, 2007)
Eragon is an orphaned farm boy whose destiny is sealed forever when a mystic stone chooses him for its keeper. This is no ordinary stone, this is the last surviving egg of the dragon race. Eragon is now the new Dragon Rider, the boy who will be a savior to the repressed peoples of the Kingdom. The Kingdom is ruled by the wicked King Galbatorix and his evil wizard Durza. Eragon, together with his mentor, Brom, the gracious dragon Saphira and the beautiful Princess Arya learn more about themselves, their responsibilities and their destinies.